PERPUSTAKAAN SEKOLAH SEBAGAI SARANA PENGEMBANGAN BUDAYA LITERASI DAN MINAT BACA SISWA DI SDN BESUK 2 PROBOLINGGO - Aulya Septa Anggita; Ririn Astutik; Evi Hosnawiyah; Nur Aisyah Rizqullah; Abdullah Adib; Devy Habibi Muhammad (As-Sulthan Journal of Education, 2026)
This study aims to analyze the development of students' reading interest through the school library at SDN Besuk 2 Probolinggo, identify the factors contributing to students' low reading interest, and describe the school's efforts to promote literacy. The study employed a qualitative approach using a case study design. The participants consisted of students, a fifth-grade teacher, and the school librarian, who were selected through purposive sampling. Data were collected through observations, in-depth interviews, and documentation, and analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the school library plays an important role in supporting literacy development through library services, a comfortable reading environment, literacy-based assignments, and reading activities before classroom instruction. However, students' participation in utilizing the library remains relatively low due to internal factors, such as motivation and reading habits, and external factors, including library facilities, family support, the school environment, and the increasing use of digital devices. The study concludes that improving students' reading interest requires sustainable literacy programs, effective library management, and strong collaboration among schools, families, and the community to foster a lasting reading culture.